Deubiquitinase enzyme STAMBP plays a broad role in both Toll-like and Nod-like receptor mediated inflammation. (October 2020) - Gangoda, Lahiru; Phan, Thanh Kha; Anand, Sushma; Hulett, Mark D; Mathivanan, Suresh
The innate immune system in mammals include pattern recognition receptors (PRRs), which initiate immune responses to microbial infection via several mechanisms. These PRRs include cell surface Toll-like receptors (TLRs) and cytosolic Nod-like receptors (NLRs) that recognizes extracellular and intracellular danger signals respectively. NLRs are poised to respond specifically to pathogens that access the host cell cytosol. The molecular mechanisms by which NLRs are activated to form inflammasomes and exert downstream inflammatory responses remain poorly understood. Additionally, very little is known about the regulation of cytosolic pathogen sensory NLR family members, except for NLRP3. Recently a deubiquitinase known as STAMBP has been implicated as a regulator of NLRP7 inflammasome assembly. We have investigated the role of STAMBP in regulation of other inflammasome components and its broader role in inflammation using genetic removal of STAMBP protein from cells using CRISPR/Cas9 gene editing and challenging these gene edited cells with an inflammatory stimuli. Our study demonstrated that STAMBP has a critical role in inflammation both in the context of NLR pathway, through NLRP stabilization and TLR pathway, through JNK signaling and downstream cytokine production. The findings indicate that STAMBP has a wider role in inflammation than previously thought to be the case.